If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3-(6*x)-(2*x) = -29 // + 29
3-(6*x)-(2*x)+29 = 0
3-6*x-2*x+29 = 0
32-8*x = 0 // - 32
-8*x = -32 // : -8
x = -32/(-8)
x = 4
x = 4
| 7-7d-4d=139 | | 5x-1/3 | | 7t+10+t=106 | | b+1+6b=57 | | -8+6t+3t=82 | | -23=-t-4t+7 | | -18=7t+6t-5 | | 13=5d-6d+1 | | -6k+6+k=1 | | 6-4d-d=1 | | 2+n+5n=68 | | 90=5k+5k-10 | | -5=-4x+2x-5 | | 7w+9-w=3 | | 7w+6+6w=6 | | 82=-5n-5n+2 | | 3-3w+2w=0 | | -51=7k-k-9 | | 2x+6+x=-27 | | 10+5t-3t=32 | | -9+a+6a=68 | | 3x+3-4x=6 | | -12=a+2a+6 | | -4+2w+6w=-52 | | a+4-2a=14 | | 2b-4-6b=20 | | -6t+2+3t=-7 | | -4d+6+d=-18 | | m+4+2m=10 | | 7+4a+7a=95 | | 10+x-6x=10 | | -88=3k+6k+2 |